Contemporary issues in ethics and information technology - Schultz, Robert A., 1942- (Hershey, PA : IRM Press, 2006)
"This book uses general ethical principles as a basis for solutions to solving ethical problems in information technology use within organizations"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Ethics; Information technology; Technology -- Moral and ethical aspects